The Role of Strategic Management in Promoting Performance in Sport Federation’s in The Kingdom of Saudi Arabia (Football Federation & Equestrian Federation) - Shujaa, Monues (The Arab Journal of Administration, 2023)
The problem of study...In determining the level of implementation of the strategic management of sports federations and its role on the performance of technical and administrative sports federations in the Kingdom of Saudi Arabia within a specified period of time. The aim of this study. To study the current situation of Saudi sport by studying the role of applying strategic management or one of its components to the performance of sport federations. The subject of the study is whether the performance of sports, such as obtaining tournaments or financial performance such as income of the federations and so on. The importance of the study... The importance of the current study is that it is a scientific addition in the field of sports management research, and can benefit from the results in directing and developing the administrative work in the sports system. The study hypothesized.... There are no significant differences between the implementation of strategic management and the development of technical and administrative performance in the sports federations, and there are no significant differences between the status of the strategy at the functional level applied in the sports federations. There are no significant differences between the formulation of the strategy and the requirements for effective implementation of performance strategies. The researcher used the descriptive approach... The researcher used the latest technology through the website www.surveymonkey.com, which specializes in the design and implementation of research questionnaires, collecting and arranging results as well as direct interviews. The results of the study...... There are differences with significant signs between the role of strategic management and the development of technical and administrative performance in the Saudi sports federations subject of study.